If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 15 = 60 + -3x Reorder the terms: 15 + 2x = 60 + -3x Solving 15 + 2x = 60 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + 2x + 3x = 60 + -3x + 3x Combine like terms: 2x + 3x = 5x 15 + 5x = 60 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + 5x = 60 + 0 15 + 5x = 60 Add '-15' to each side of the equation. 15 + -15 + 5x = 60 + -15 Combine like terms: 15 + -15 = 0 0 + 5x = 60 + -15 5x = 60 + -15 Combine like terms: 60 + -15 = 45 5x = 45 Divide each side by '5'. x = 9 Simplifying x = 9
| 5x-30+6=7x-6 | | 8x+19=9x+13 | | 4(2k-5)-5(4k+1)=2-2(k+3) | | -2n-10+3=-n+5 | | 2x+19=9x+47 | | 7x=78-6x | | 20x-30=5y | | 3xn+5=17 | | X=25+0.75x | | b+3=-18 | | 9a-3-11=49 | | 7x+19=69-3x | | 12x=72x | | X^3-7x^2+31x-25=0 | | 13x-2(x+2)=8x+1 | | 180+50x=1320 | | 10+3x+(-x^2)=0 | | 7d-2e=19 | | (3x-5)+70=x | | 9-7a=5-6a-1a | | 150+50x=1090 | | 5(x-3)-4(x+2)=3(1-2x) | | 3y-5+8y+20=180 | | 10+3+(-x^2)=0 | | 6+4x=7x+6 | | X-(4x-7)=5c-(x+21) | | 27+4x=3x | | 6-3(2x+2)-3(5x-6)=5(x+7)+8x | | (2p+4)+5(p-1)-(p-7)= | | 5p*2+3=g | | 3x+19=24-2x | | 5(2x-3)=4x+7 |